2021
DOI: 10.21203/rs.3.rs-51719/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parasitism of Aedes albopictus by Ascogregarina taiwanensis lowers its competitive ability against Aedes triseriatus.

Abstract: Background: Mosquitoes are vectors for diseases that significantly impact the human population such as dengue, malaria and La Crosse virus. When multiple mosquito species are present, the competition between species may alter population dynamics as well as disease spread. Two mosquito species, Aedes albopictus and Aedes triseriatus, both inhabit areas where La Crosse virus is found. Infection of Aedes albopictus by the parasite Ascogregarina taiwanensis and Aedes triseriatus by the parasite Ascogregarina barret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…albopictus infected with Ascogregarina reduces its competitiveness in the habitat with different larvae such as Ae. triseriatus [39]. In addition, it has already been shown that the propitious infection by Ascogregarinas can impact the Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus infected with Ascogregarina reduces its competitiveness in the habitat with different larvae such as Ae. triseriatus [39]. In addition, it has already been shown that the propitious infection by Ascogregarinas can impact the Ae.…”
Section: Discussionmentioning
confidence: 99%